Risk factors for musculoskeletal injuries in elite junior tennis players: a systematic review - Oosterhoff, J. H. F.; Gouttebarge, V.; Moen, M.; Staal, J. B.; Kerkhoffs, G. M. M. J.; Tol, J. L.; Pluim, B. M. (Journal of Sports Sciences, 2019)
The objective was to systematically review the literature on risk factors and prevention programs for musculoskeletal injuries among tennis players. PubmedMedline, Embase, CINAHL, Cochrane, SportDiscus were searched up to February 2017. Experts in clinical and epidemiological medicine were contacted to obtain additional studies.